Magnetostratigraphy of the Eocene-Oligocene Interval: New paleoenvironmental interpretations on the closure of the Neotethys Ocean - Souza, Ana Paula de Martini de (2020)
The Eocene-Oligocene Transition (EOT) is characterized as a period of drastic climate change from a greenhouse environment of the Paleocene-Eocene to the icehouse climate of the Oligocene. This period is also known for the peculiar oceanographic conditions evidenced by the oceanic reorganization, biotic turnovers and isotopic excursions. It is hypothesized that the gradual closure of Neotethys Ocean changed the southern part of the global Eocene Neotethys Subtropical Current (STENT) to a counter-clockwise Gyre in the Indian Ocean and closed its connection with the Atlantic Ocean. If this hypothesis is correct, the sediments from Neotethys would be sensitive to changes in global circulation containing evidence of this paleoenvironment. In this work, techniques of environmental magnetism, rock magnetism and geochemistry were applied for two different sections, one corresponding (1) the marine sediments recovered from western equatorial Indian Ocean during the Deep Sea Drilling Program (DSDP) expedition Hole 709C, Leg115 and (2) the Portella Colla section, at the Caltavuturo formation at Sicily, Italy, in order to compare how the environmental changes around the EOT is recorded in both areas. The magnetostratigraphy revealed an age range of studied sediments from the Mid Eocene Climatic Optimum (MECO) to EOT in the Indian Ocean and from the late Priabonian to Rupelian at Portella Colla. Environmental magnetic properties indicate decreasing magnetic grain size from MECO to EOT suggesting differential input. The rock magnetism data indicates a higher paramagnetic detrital contribution for Portella Colla, while Hole 790C presents peaks of high productivity with main contribution of biogenic magnetite of single domain state (SD), which suggests periods of active current. Further, geochemical and mineralogical changes support this observation.